66.8k views
2 votes
Rewrite the expression in z to the n power. The expression I was given is: 1 over z to the negative 1 half power.

User Leaann
by
4.7k points

1 Answer

1 vote

Answer:

The equivalent expression is;


\frac{1}{z^{-(1)/(2)}}=z^{(1)/(2)}

Explanation:

The given expression is:



\frac{1}{z^{-(1)/(2) }}

Recall that:


(1)/(a^(-m))=a^m


In our case,
a=z and
m=(1)/(2).


We use this property of exponent to obtain;


\frac{1}{z^{-(1)/(2)}}=z^{(1)/(2)}


User Shinto Joseph
by
4.4k points